Mussel periostracum protects against shell dissolution - Alisha M. Saley; Aaron T. Ninokawa; Abigail Doan; Brian Gaylord (PLoS ONE, 2025)
Reductions to seawater pH challenge the shell integrity of marine calcifiers. Many molluscs have an external organic layer (the periostracum) that limits exposure of underlying shell to the outside environment, which could potentially help combat shell dissolution under corrosive seawater conditions. We tested this hypothesis in adult California mussels, Mytilus californianus. We quantified shell dissolution rates as a function of periostracum cover across three levels of reduced pH (7.7, 7.5, and 7.4 on the total scale). Since periostracum can also be eroded over time, we additionally conducted a first-pass examination of whether differing surface textures induced by abrasional processes might influence dissolution rates. We contextualized this set of experiments with measurements of mussel periostracum cover in multiple intertidal habitats. Our results indicate a threefold reduction in shell dissolution rate as periostracum cover increases from 10 to 85% of shell surface area. Dissolution was higher in lower-pH treatments and in treatments where periostracum removal resulted in shells with rougher surface texture, potentially due to increased microtopographic surface area of underlying shell exposed to corrosive seawater. Periostracum loss in the field was greater for mussels at higher shoreline elevations and in sunnier locations, where heat, ultraviolet radiation, and desiccation at low tide may weaken attachment of the periostracum to the shell and. These findings highlight the potential for protective structures of marine organisms to help confront increasingly acute global environmental stressors.